Pulmonary Nocardiosis Induced by Long-Term Use of Steroids on a Bronchiectasis Backgroung - Levent Özdemir; Burcu Özdemir; Mustafa Temelli; Osman Nuri Hatipoğlu (Haseki Tıp Bülteni)
A 45-year-old male was assessed with the complaints of cough, sputum, fever, shortness of breath, tingling and burning in both legs. In his history, he had frequent hospitalizations and steroid use. Respiratory system examination revealed inspiratory and expiratory crackles on bilateral lower-middle zones and expiration rhoncus. Laboratory examination revealed leukocytosis and elevated CRP levels; serology for HIV was reported negative. Computed tomography showed diffuse interstitial pneumonia. Electromyography (EMG) showed lower extremity muscle activation compatible with myopathy. Acid-fast bacilli was negative (three consecutive negative microscopy results) and no reproduction was detected in the culture. Nocardia spp. growth was detected in sputum culture. According to the antibiogram results, he was treated with doxycycline, trimethoprim and sulfamethoxazole for 6 months. At the end of treatment, the lesions were found to be regressed on computed tomography. In conclusion, considering the high frequency of bronchiectasis in our country, the fact that nocardia may develop due to inappropriate long-term steroid use during an attack should be kept in mind.